Nearer my mall to thee: The decline of the Johannesburg Central Business District and the emergence of the neo-apartheid city - Beavon, K. (My University, 1998)
Many people subscribe to the notion that the Johannesburg central business district, or CBD, has declined substantially in recent years. A closer examination of the available data, however, suggests that the process has in fact been evident for some 40 years (Lauf 1959). By the 1950s, white residential growth had already begun to bulge out to the north (Figure 1), while the 1960s saw the beginnings of a similar movement of office accommodation. Furthermore, some of the major developments that emerged in the downtown area during the 1970s, and that were intended to reinforce the status of the CBD, in fact did much to hasten the decline of downtown retailing. The neo-apartheid city that we see unfolding today has deep historical roots.
African Studies Seminar series. Paper presented 5 October, 1998
Keywords: Johannesburg (South Africa); Central business districts. South Africa. Johannesburg